Preparation and High-Temperature Structural Stability of Al₂O₃-Coated SiO₂ Large Hollow Particles - Champreda, Marisa; Pereira, Ana; García, Fredy E. (Journal of Green Energy and Environmental Engineering, 2026)
Suppressing the high-temperature sintering of nanoporous thermal insulation materials and enhancing their structural stability is a primary step in extending their service temperature. Al₂O₃-coated SiO₂ large hollow particles (large hollow particle SiO₂@Al₂O₃, diameter ≈130 nm, wall thickness ≈15 nm) were prepared via a hard-template-assisted precipitation method. By synergistically utilizing the anti-sintering property of Al₂O₃ and the low thermal conductivity and low density advantages of SiO₂ hollow structures, the challenge of balancing thermal conductivity and structural thermal stability in traditional thermal insulation materials was addressed. In situ TEM results indicate that when the Al₂O₃ coating content was 3.9% (mass fraction), the particles maintained intact hollow structures after heat treatment at 1200°C for 30 min, with a shrinkage rate <9%; whereas uncoated SiO₂ large hollow particles significantly shrank and ruptured within 2 min. The effective thermal conductivity of this sample was 0.036 W·m⁻¹·K⁻¹ at room temperature and only increased to 0.074 W·m⁻¹·K⁻¹ at 1100°C, with a density as low as 0.2686 g·cm⁻³, representing a 14% reduction compared to 10 nm solid SiO₂ particles (density 0.3128 g·cm⁻³). Based on molecular dynamics simulations, the high-temperature evolution behavior of these composite particles during heating was systematically revealed, elucidating the mechanism by which the Al₂O₃ shell suppresses the diffusion of liquid-like atoms. This preparation strategy provides experimental and theoretical foundations for the controllable fabrication of lightweight, high-flowability high-temperature thermal insulation powders.